2013
DOI: 10.1021/la402832b
|View full text |Cite
|
Sign up to set email alerts
|

Combining Nitrogen, Argon, and Water Adsorption for Advanced Characterization of Ordered Mesoporous Carbons (CMKs) and Periodic Mesoporous Organosilicas (PMOs)

Abstract: Ordered mesoporous CMK carbons and periodic mesoporous organosilica (PMO) materials have been characterized by combining nitrogen (77.4 K) and argon (87.3 K) adsorption with recently developed quenched solid density functional theory (QSDFT). Systematic, high-resolution water adsorption experiments have been performed in the temperature range from 298 to 318 K in order to ascertain the effect of surface chemistry (using periodic mesoporous organosilicas (PMOs) of given pore size) and pore size/pore geometry (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
136
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(152 citation statements)
references
References 58 publications
11
136
0
5
Order By: Relevance
“…They found that adsorption of water is very sensitive to surface heterogeneity but the physical structure has limited effects in the low pressure region. Similar conclusions were also drawn by Thommes et al [25,26], who proposed water as a probe to characterize the surface chemistry of carbon materials.…”
Section: Introductionsupporting
confidence: 85%
“…They found that adsorption of water is very sensitive to surface heterogeneity but the physical structure has limited effects in the low pressure region. Similar conclusions were also drawn by Thommes et al [25,26], who proposed water as a probe to characterize the surface chemistry of carbon materials.…”
Section: Introductionsupporting
confidence: 85%
“…Another consequence of confinement effects is the formation of water clusters, which play a significant role in the stabilization of water in hydrophobic carbon micro and mesopores. [31,32] By forming clusters of 5 or more water molecules (cluster size of ∼ 1 nm), [31,[33][34][35]] the affinity of the water molecules can be transformed from hydrophillic to hydrophobic, [33] making their interaction with the CNT walls more favorable. While many previous studies have explored the mechanics, kinetics, and energetics of the entry of water molecules into uncapped single walled CNTs, [30,[36][37][38] the likelihood that a water molecule can enter the 3 inner region of a capped multiwalled CNT via wall defects is low (since the openings in the CNT walls are likely smaller than the cluster size), meaning that the exohedral physisorption of water is expected.…”
mentioning
confidence: 99%
“…However, we do not understand the validity of the cluster-associated filling mechanism to mesoporous carbons, although adsorption of water in mesopores of 30 nm in the width cannot be observed below P/P 0 = 0.95 (Hanzawa and Kaneko 1997). A recent study on water adsorbed on ordered mesoporous carbon showed a unique stepwise adsorption isotherm which can be ascribed to adsorption in micropores and mesopores (Thommes et al 2013). We need to clarify the applicability of the cluster-associated filling mechanism to small mesopores.…”
Section: Introductionmentioning
confidence: 72%
“…Then, understanding of the interaction of water with nanoporous carbon can contribute to develop a new water related technology. However, the water-carbon interaction is not necessarily understood regardless of active studies for a long time (Thommes et al 2013;Müller et al 2013;Mowla et al 2003;Lie et al 2007;Striolo 2011;Nguyen and Bhatia 2011).…”
Section: Introductionmentioning
confidence: 99%